OFFSHORE DERRICK SAFETY EVALUATION BASED ON THE TEST AND SIMULATION ANALYSIS - HUANG ZhiQiang; JI SuDan; ZHANG Bo; QIU ChengSong; XI YuXi (Jixie qiangdu)
In order to evaluate the safety of the derrick,taking a tower drilling rig derrick as the prototype,scaling factor and steel products style was confirmed,and laboratory model derrick was established. Static and modal finite element simulation analysis and test was done and got the stress distribution rule,the first ten natural frequency and modal modes. Comparing the results of simulation and test,the test results agree well with the simulation results,the error in the limitation,which verify that the finite element simulation means are correct. At last,the safety evaluation was undertaken on the model derrick,the evaluation results of modal derrick was extrapolated to the actual derrick according to the similarity relation,and then the safety assessment of the prototype derrick was done. These provide the methods to study the safe bearing capacity,structure optimization design and using of the real derrick.